Influence of Pancreo-Plant on the histological parameters of the liver in conditions of acute toxic hepatitis - L. M. Trutaieva (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Toxic liver damage is the most problematic for pharmacotherapy and, accordingly, the normalization of the patient’s condition. Most often, hepatotoxins include alcohol, drugs, household and industrial toxins, the effect of which on the liver leads to the development of hepatocyte necrosis. The peculiarity of drug toxic hepatitis is a wide range of clinical manifestations, the absence of unambiguous diagnostic methods, frequent poor prognosis, which makes toxic hepatitis one of the most difficult problems in clinical practice. A promising drug for the treatment of toxic liver damage is a multicomponent herbal remedy, which is currently produced by a domestic manufacturer in the form of a dietary supplement.